PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APLIKASI MEGADIK UNTUK MENINGKATKAN PEMAHAMAN SISWA DALAM MATERI KLASIFIKASI GAYA MATA PELAJARAN IPA KELAS IV - Arfinya, Salsabila kusuma; Regina Lichteria Panjaitan; Sujana, Atep (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop an interactive multimedia application-based learning media MEGADIK (Classifying Forces Around Us) to improve the understanding of fourth-grade elementary school students on the material of force classification in science subjects. The study uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 41 fourth-grade students, a class teacher, and two validators, material experts and media experts. The research instruments included a validation questionnaire, student response questionnaire, interviews, and pretest and posttest tests. The results of the media expert validation showed a feasibility percentage of 96% (very feasible category), while the material expert validation obtained 95% (appropriate material category). The effectiveness test through N-gain analysis produced an average score of 0.60 (moderate category) or 60.25% (quite effective) with an average increase in value from 52.59 (pretest) to 81.15 (posttest). Student responses to the application showed a very good category in all aspects, with the highest score in ease of use of 92.93%. These findings demonstrate that MEGADIK can concretely visualize abstract concepts, increase motivation, and encourage active student engagement. This application is recommended as an alternative learning medium for science instruction in elementary schools.